FINANCIAL CONDITION ANALYSIS OF REGENCY/CITY IN NORTH MALUKU PROVINCE FOR THE PERIOD 2019-2023 - Tri Widodo; Herlin Tundjung Setijaningsih (Graduate Program of Universitas Tarumanagara, 2026)
The financial condition of a region reflects its fiscal capacity in implementing fiscal decentralization. An analysis of regional financial conditions is essential as an evaluation process of the current financial performance and is expected to provide guidance for future regional financial planning. One of the most commonly used studies to measure the financial condition of a region is Kenneth Brown’s 10-Point Test. This study aims to determine the financial condition of regencies and cities in the Province of North Maluku during the five-year period from 2019 to 2023, both during and after the COVID-19 pandemic. This research employs a descriptive quantitative method using secondary data related to the financial statements of regencies and cities in North Maluku Province. The study examines eight regencies and two cities using Brown’s 10-Point Test, with indicators derived from the modified models of Kenneth Brown and Maher & Nollenberger (2009). The results indicate that, on average, the financial condition of regencies and cities in North Maluku Province falls within the best category, although there was a decline in the financial score in 2020 compared to 2019. This decline was primarily due to the impact of the COVID-19 pandemic across most regions. However, from 2021 to 2023, the financial condition of the regencies and cities in North Maluku Province showed an upward trend, suggesting that these areas had begun recovering from the post-pandemic financial downturn. The decline in regional financial conditions was influenced by low fiscal independence, inefficient regional spending that resulted in low operating surpluses and/or increasing budget deficits, growing debt levels and debt service obligations, as well as low cash stability. Therefore, local governments need to enhance Regional Original Income (PAD) and focus regional expenditure on long-term infrastructure development and initiatives that empower and strengthen local economies, as well as prepare financial reserves to anticipate potential fiscal emergencies.